Evaluasi Kebijakan 5 Hari Kerja Terhadap Pencapaian Standar Pelayanan Minimal Pada Dinas Pendidikan Kota Mataram - Jauji, Ibnu; Wilian, Sudirman; Waluyo, Untung (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This study aims to reveal employee performance on the effectiveness of the 5 working day policy in improving the implementation of the Minimum Service Standards at the Mataram City Education Office and to explain the factors inhibiting the implementation of 5 working days in relation to the achievement of Minimum Service Standards at the Mataram City Education Office. This research uses a qualitative approach with descriptive methods. This research was conducted at the Mataram City Education Office. Collecting data using observation, interviews and documentation. The data analysis technique uses three activity lines, namely data reduction, data presentation and conclusion drawing. Validity data using analysis techniques of credibility, transferability, dependability and confirmability. The results of this study indicate that the five-day work policy, both regarding the use of time and work discipline, work intensity, work initiative, and work atmosphere in the five working day policy collectively contributes positively to the work productivity of the Mataram City national education office employees. Employees feel happy with the policies implemented by the Education Office so that employee performance can increase towards achieving minimum service standards.